FOSTERING PROSOCIAL BEHAVIOURS OF EARLY CHILDHOOD THROUGH GROUP GUIDANCE WITH A CLIENT CENTERED THERAPY APPROACH - Sari, Azmatul Khairiah; Neviyarni, Neviyarni; Karneli, Yeni; Netrawati, Netrawati (Journal of Early Childhood Education (JECE), 2020)
This study aims to see how group guidance with a client-centred therapy approach in early childhood improves prosocial behaviour. This study uses library research method. Data analysis in this study used a narrative synthesis analysis. The results of this study indicate that prosocial behaviour is behaviour that is displayed when interacting with other people where children spontaneously help others. Prosocial behaviour is displayed by early childhood to the friends, parents, teachers and the surrounding community. Group guidance with a client-centred therapy approach provides counselling techniques to make early childhood become individuals who can understand their potential and actualize their social relationships. In the implementation of group guidance, early childhood will interact and communicate with each other; the counsellor can ask them to practice these prosocial behaviours. Either by answering questions if (...) then (...) or by telling how he should act when faced with a situation that requires displaying this prosocial behaviour.